Climate Change and The Latest Scientific Efforts to Understand It - Kuzibaeva, Ozodkhon; Xomidova, Nargiza; Muminov, Doniyor; Boratov, Alijon; Zebiniso Nazarova, Jamshid Mahkamov; Imomov, Elyor; Zoxidov, Sarvar; Umarov, Javohir (Journal of Neonatal Surgery, 2025)
Climate change affects natural landscapes and is being studied based on various scenarios and models. This article examines the impact of climate change on natural landscape complexes of the Republic of Uzbekistan, particularly in the Fergana Depression. It also highlights the measures being taken to mitigate the negative effects of climate change